Tinjauan Yuridis Perlindungan Hukum Bagi Konsumen Terhadap Produk Obat-Obatan Ilegal (Studi Kasus : BPOM Medan) - Muhammad Ridho Al Hasymi Daulay; Utary Maharani Barus; Rafiqi Rafiqi (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Consumer protection aims to foster awareness of business people about the importance of consumer protection so that honest and responsible attitudes in the business grow. Medicines and food products are supervised by the Food and Drug Supervisory Agency or abbreviated as POM, which is in charge of overseeing the distribution of medicines and foods in Indonesia. The method used in this study is the method of Library Research and Field Research. Legal protection for consumers who use illegal drug products is by means of consumers being able to complain about their problems through litigation, this is explained in Article 45 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection and and non-litigation namely legal efforts outside the court can be through the Consumer Dispute Settlement Agency (BPSK) established and regulated in the Consumer Protection Act. The responsibility given by the Food and Drug Supervisory Agency (BPOM) to the community, namely the Food and Drug Supervisory Agency (BPOM), will take firm action against producers or business actors who circulate illegal drugs in this case drugs that do not have a marketing authorization (TIE), drugs, substandart, fake drugs, or expired drugs.